Subtle structure of streamers under conditions resembling those of Transient Luminous Events - Błęcki, J.S.; Mizerski, K.A. (Archives of Mechanics, 2018)
The paper presents a brief review of the observational facts related to plasma filamentation in astrophysics and the subtle structures of plasma in Transient Luminous Events (TLE’s) and an analysis of the physical mechanism that could contribute to formation of filaments in plasma inside streamers. The values of physical parameters are assumed such as to resemble the physical conditions in streamers of the TLE’s. Estimates of the typical spatial scales of these structures and temporal characteristics of filament formation are given. The analysis concerns a non-magnetic mechanism based on a form of non-relativistic dissipative instability and the electron-nitrogen collisional 2Πg resonance. It is argued that the influence of the magnetic field is negligible at the leading order at least up to the altitudes of about 65–70 km. Under the conditions related to those in plasma inside the TLE’s, derived based on the current knowledge of physical parameters within the electric discharges, the identified dissipative-resonant instability is demonstrated to be the only/most vigorous linear instability developing in the system. It results in periodic plasma density distribution in the direction transverse to the electric field. The obtained time scales of the instability development are quick and proportional to the inverse of the ion-neutral collision frequency, 1/νi, whereas the proposed spatial scale of the density stripes/filaments is proportional to the electron temperature and inversely proportional to the speed of the discharge.